Pemilihan Fungsi Sosial dan Fungsi Rohani Bagi Korban Penyalahgunaan Narkoba di Yayasan Amanat Agung Medan - Malida Putri; Bryan Egianta Tarigan (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Recovery  is  a  process  that  a  drug  addict  must  go  through  if  he  wants  to  be  completely  cured  of  his addiction.  Recovery  does  not  mean  just  stopping  using  (drugs),  recovery  must  be  understood  as  the creation  of  a  newlifestyle,  thus  it  will  be  easier  for  someone  to  decide  not  to  use  (drugs)  again.  In recovery  there  are  three  things  that  must  be  considered,  namely  avoiding  high-risk  situations,  learning how  to  relax,  and  telling  the  truth.  Recovery  demands  total  honesty,  that  is,  if  you  want  to  recover,  you have  to  be  one  hundred  percent  honest  with  the  people  who  support  you,  such  as  family,  doctors, therapists,  etc.  If  you  can't  be  honest  with  them  then  the  recovery  won't  go  well.  Being  totally  honest means not givinghis addictive  nature  a place to hide. If you lie, it means you have opened the  door for relapse.  An  opportunity  to  change  life  can  be  seen  as  an  opportunity  to  change  life.  Changing  lives  is what makes recovery difficult but also profitable. Recovery is difficult because a person has to change his or her life, and all changes are difficult, even if it turns out to be good. Recovery is beneficial because a person gets the opportunity to change his life. If we take the opportunity to change, then we will look back and  reflect  on  our addiction as  the  one  good  thing  that  ever  happened  in  life.  In  recovery,  people  often describe  themselves  as  grateful  addicts.  Why  should  someone  be  grateful  to  have  experienced  an addiction  because  starting  from  that  addiction  they  are  then  helped  to  find  the  peace  and  serenity  that many people seek. Recovery (recovery) can encourage a person to change his life